Comparison of greenhouse and open field cultivations across China: Soil characteristics, contamination and microbial diversity. (December 2018) - Sun, Jianteng; Pan, Lili; Li, Zhiheng; Zeng, Qingtao; Wang, Lingwen; Zhu, Lizhong
Abstract: A national scale survey was conducted to determine an array of inorganic and organic contaminants in agricultural soils from two cultivation modes (greenhouse vs. open field) in 20 provinces across China. The investigated contaminants include organochlorine pesticides (OCPs), phthalate esters (PAEs), polycyclic aromatic hydrocarbons (PAHs), lead (Pb), zinc (Zn), copper (Cu) and cadmium (Cd). The large amounts of agrochemicals used and special cultivation mode in greenhouse caused substantial soil pollution and deterioration of soil quality. Mean concentrations of both OCPs and PAEs in greenhouse soil were approximately 100% higher than those in open field. The pH values were 6.85 ± 1.04 and 7.34 ± 0.84 for greenhouse and open field, respectively ( p > 0.05). The soil microbial community was predicted to be affected by pollution in greenhouse through the PICRUSt analysis of 16s rRNA sequences. The 12 variables including various chemicals and soil properties together explained 15% of the observed variation in the community composition. In the studied variables, PAEs and lead were the primary factors affecting microbial diversity in greenhouse soils, while pH had the greatest impact on the microbial community in open field soils. These findings enhanced our understanding of the environmental impact and contamination management of greenhouses worldwide. Graphical abstract: Image 1 Highlights: The primary contaminants in greenhouse and open field soil in China were determined. OCPs and PAEs in greenhouse soil were generally higher than those in open field. Soil microbial communities changed by the greenhouse cultivation mode. Abstract : This national scale survey revealed overall pollution status and effect in agricultural soils from greenhouse and open field in 20 provinces across China.